Effects of spinal manipulation and pain education on pain in patients with chronic low back pain: a protocol of randomized sham-controlled trial - Clécio Vier; Marcelo Anderson Bracht; Marcos Lisboa Neves; Maíra Junkes-Cunha; Adair Roberto Soares Santos (Integrative Medicine Research)
Background: Low back pain (LBP) has more than doubled in the last 20 years, probably influenced by biopsychosocial factors. Noninvasive treatments have been applied in individuals with chronic nonspecific LBP as spinal manipulation and pain education. However, the neurophysiological effects of these treatments are not clear. The aim of this research is to verify the pain control, functional and neurophysiological effects of spinal manipulation, and pain education in individuals with chronic nonspecific LBP. Methods: This research is an assessor and subject blinded, 2-arm, randomized sham-controlled trial and will be conducted at Governador Celso Ramos Hospital, Florianópolis, Brazil. One hundred and twenty-eight individuals with chronic nonspecific LBP will be recruited for this study. Individuals will be randomly allocated into one of the two groups: (1) spinal manipulation plus pain education or (2) sham treatment plus pain education. Each group will be received two sessions per week over six weeks of treatment. The measures will be applied at baseline, six weeks, and three months after randomization. The primary outcome will be a pain intensity at six weeks postrandomization. Secondary outcomes will be pressure pain threshold, disability, fear and avoidance beliefs, kinesiophobia, risk of poor prognosis, quality of life, and inflammatory biomarkers. Discussion: Evidence has shown that psychosocial factors are more involved in chronic pain than we thought a few years ago. Then, studies investigating both functional and neurophysiological effects of these interventions to evaluate the effectiveness of treatment and what else is happening at the cellular level in nervous system are needed. Keywords: Low back pain, Musculoskeletal manipulations, Neurophysiology, Education, Randomized controlled trial